Pengaruh Literasi Keuangan, Sikap Keuangan, dan Self Efficacy Terhadap Perilaku Pengelolaan Keuangan Ibu Rumah Tangga - Melisa, Anindhitiya Sofi; Dewandaru, Bothy; Sudjiono (Jurnal Ilmiah Aset, 2024)
The aim of this research is to determine the influence of financial literacy, financial attitudes and self-efficacy on financial management behavior among housewives in RT 04 Dusun Turi, Kembangan Village. This type of research uses quantitative research. Quantitative research is research using survey data that is quantified and statistically analyzed. Classical assumption testing, multiple linear regression analysis, and hypothesis testing are the test instruments used in this research. The financial literacy variable has a positive and insignificant effect on the dependent variable, namely financial management behavior. The financial attitude variable has a positive and insignificant effect on the dependent variable, namely financial management behavior. The independent variable, namely self-efficacy, has a positive and significant effect on the dependent variable, namely financial management behavior. Meanwhile, financial literacy, financial attitudes and self-efficacy simultaneously have a positive and insignificant influence on financial management behavior among housewives in RT 04 Dusun Turi, Kembangan Village.